Emperor Basil II and the Awarding of Byzantine Honorific Titles to Bulgarians in the Course of the Conquest of Bulgaria (976–1018) - Kanev, Nikolay (Studia Ceranea, 2019)
This article examines the question about the policy of honouring members of the Bulgarian imperial family and Bulgarian aristocracy with Byzantine honorific titles pursued by Emperor Basil II Boulgaroktonos (976–1025) in the course of the conquest of Bulgaria. It outlines the scale of this policy of Basil II – its goals and the reasons for adopting it. A review of the place and the importance of the particular titles in the rank hierarchy of Byzantium is presented. The comparison with other regions and cases of conferring Byzantine honorific titles clearly shows how crucially important the conquest of Bulgaria was: it is evident from the concessions the Emperor was ready to make to the Bulgarian ruling elite.